Retention and absorption of boron salts solution of ten mexican woods - Sotomayor-Castellanos, Javier-Ramón; Villaseñor-Aguilar, José-María (Acta Universitaria, 2016)
oron salts are a wood protector agent with a wide spectrum in their fungicidal and insecticide action and of low toxicity, odorless, colorless and nonflammable, and their application is one of the most effective preservation strategies. This research aims to determine the density of wood, absorption and retention of the boron salts of ten Mexican woods. The working hypothesis proposed in this investigation is that wood retention capacity of boron salts depends mainly on the species and is independent of its density and porosity. Thirty liters of boron salts solution with a concentration of 3 % were prepared, the wood specimens were impregnated by following the “hot-cold bath” method. It was designed an experiment that compared means of the density of wood, the absorption and the retention, as the response variables, assessed for each one of the ten wood species. Wood species was considered as the variation factor. Absorption of Boron salts varied between 136 kg/m3 and 476 kg/m3. Average values of the boron salts retention for all species were higher than lower retention toxicity limit reported in previous researches (0.2 kg/m3 to 4.7 kg/m3). It was concluded that each species has different boron salts retention. Absorption capacity is specific to each species and it is not related to the wood density.